A simulation model for investigation of operation of elevator's up-peak. Issue 3 (2nd July 2020) - Xiang, Shousheng; Arashpour, Mehrdad; Wakefield, Ron
ABSTRACT: Elevator planning is a key factor for high-rise building construction and building design. Up-peak load is a common phenomenon in building elevator design and operation. For example, in the morning, passengers want to take an elevator to their working floors. Up-peak is often used as the critical traffic period for elevator planning in a building. Two parameters are usually used to plan elevators: the elevator's round-trip time and average waiting time. To easily and accurately obtain the values of these two parameters during up-peak load, we propose an agent-based discrete-event simulation model. The validation of the baseline model is undertaken using deterministic data, after which the model is expanded to the random situation. Then, we use an event to define any arrival pattern of passengers. Finally, we describe various model elements to carry out simulation in other cases. A number of practical examples show that the model can be used as an elevator planning tool for building design and construction.